PROBLEMS OF TRANSITION TO AN INNOVATIVE ECONOMY IN UZBEKISTAN - Komilova Dilafruz Rustam qizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article explores the transition to an innovative economy in Uzbekistan and the role of innovation in the country’s economic development. The necessity of implementing innovation policies, effectively attracting innovative investments, and developing innovation infrastructure is discussed.